Serotonin receptor subtypes in depression: evidence from studies in neuroendocrine regulation. - Cowen, P (1993)
Serotonin (5-HT) neuroendocrine tests are a valid and acceptable means of measuring 5-HT neurotransmission in humans. Recently, the availability of selective 5-HT receptor ligands has allowed the assessment of specific 5-HT receptor subtype function using neuroendocrine methods. Studies with selective antagonists have shown that the endocrine responses to the 5-HT precursor L-tryptophan (LTP) are mediated via postsynaptic 5-HT1A receptors, whereas endocrine responses produced by the 5-HT-releasing agent d-fenfluramine involve postsynaptic 5-HT2/1C receptors. Endocrine responses to both LTP and fenfluramine are consistently decreased in depressive illness. In contrast, endocrine responses to direct 5-HT1A and 5-HT2/1C receptor agonists are not consistently attenuated in depressed patients. The current data suggest that depressive illness is associated with an impairment of 5-HT neurotransmission that involves decreased 5-HT release rather than altered sensitivity of postsynaptic 5-HT receptors.